Human Mitochondrial Cytochrome b Variants Studied in Yeast: Not All Are Silent Polymorphisms. Issue 9 (27th June 2016) - Song, Zehua; Laleve, Anaïs; Vallières, Cindy; McGeehan, John E.; Lloyd, Rhiannon E.; Meunier, Brigitte
Abstract : Although human MT‐CYB‐variants frequently occur in the healthy and diseased tissues, for most, a definitive role remains elusive. Here, we present a systematic analysis of the effect of several human MT‐CYB‐variants on yeast mitochondrial complex III properties. Several variants previously reported as "silent", including the ubiquinone‐binding‐site variation m.14798T>C (p.Phe18Leu), significantly modified the activity/drug sensitivity of yeast complex III, suggesting a greater role for MT‐CYB‐variants in human disease than previously thought. Yeast (4PD4‐blue) and bovine (1PP9‐pink) complex III are shown. ABSTRACT: Variations in mitochondrial DNA (mtDNA) cytochrome b ( mt‐cyb ) are frequently found within the healthy population, but also occur within a spectrum of mitochondrial and common diseases. mt‐cyb encodes the core subunit (MT‐CYB) of complex III, a central component of the oxidative phosphorylation system that drives cellular energy production and homeostasis. Despite significant efforts, most mt‐cyb variations identified are not matched with corresponding biochemical data, so their functional and pathogenic consequences in humans remain elusive. While human mtDNA is recalcitrant to genetic manipulation, it is possible to introduce human‐associated point mutations into yeast mtDNA. Using this system, we reveal direct links between human mt‐cyb variations in key catalytic domains of MT‐CYB and significant changes to complex III activity or drug sensitivity. Strikingly, m.15257G>A (p.Asp171Asn) increased the sensitivity of yeast to the antimalarial drug atovaquone, and m.14798T>C (p.Phe18Leu) enhanced the sensitivity of yeast to the antidepressant drug clomipramine. We demonstrate that while a small number of mt‐cyb variations had no functional effect, others have the capacity to alter complex III properties, suggesting they could play a wider role in human health and disease than previously thought. This compendium of new mt‐cyb ‐biochemical relationships in yeast provides a resource for future investigations in humans.